2021
DOI: 10.3390/ijerph18179019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Income, Density, and Population Size on PM2.5 Pollutions: A Scaling Analysis of 254 Large Cities in Six Developed Countries

Abstract: Despite numerous studies on multiple socio-economic factors influencing urban PM2.5 pollution in China, only a few comparable studies have focused on developed countries. We analyzed the impact of three major socio-economic factors (i.e., income per capita, population density, and population size of a city) on PM2.5 concentrations for 254 cities from six developed countries. We used the Stochastic Impacts by Regression on Population, Affluence and Technology (STIRPAT) model with three separate data sets coveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
2
0
1
Order By: Relevance
“…Notably, anxiety itself has been linked to a higher likelihood of developing SS ( 13 ). Furthermore, studies have indicated that as the population density of cities increases, so does the concentration of PM 2.5 ( 131 ). Through experimental verification, researchers have demonstrated that PM 2.5 can activate the skin’s inflammatory process, resulting in the release of inflammatory factors such as TNF-a and IL-1.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, anxiety itself has been linked to a higher likelihood of developing SS ( 13 ). Furthermore, studies have indicated that as the population density of cities increases, so does the concentration of PM 2.5 ( 131 ). Through experimental verification, researchers have demonstrated that PM 2.5 can activate the skin’s inflammatory process, resulting in the release of inflammatory factors such as TNF-a and IL-1.…”
Section: Discussionmentioning
confidence: 99%
“…In areas where ACRB is intense, there was a three-fold increase in ARI, and children under 5 years were the most vulnerable ( 8 ). The increased levels of PM 2.5 had a significant association with population density ( 39 ). Spatial analysis indicated that the heavily populated states, particularly in the Indo-Gangetic plains, to have high concentrations (>100 μg/m 3 ) of PM 2.5 , suggesting the strong interplay between population density and increased PM 2.5 levels in increasing the prevalence of ARI among children under 5 years in India.…”
Section: Discussionmentioning
confidence: 99%
“…Salah satu penyebab dari pola penurunan kesehatan ini adalah karena banyaknya polutan yang terhisap ke dalam tubuh manusia sehingga menimbulkan berbagai gangguan pada metabolisme tubuh [1]. Fenomena ini sangat terlihat dampaknya di kota-kota besar, dan hal ini ditengarai berhubungan dengan padatnya populasi penduduk di wilayah perkotaan [2]. Secara umum, populasi penduduk di kota-kota besar di berbagai negara terus bertambah, dan hal ini juga menyebabkan ekskalasi aktivitas yang meliputi aktivitas produksi, transportasi, rekreasi dan lainnya.…”
Section: Pendahuluanunclassified